A Multicultural Portrait of Colonial Life - Washburne, Carolyn Kott (Marshall Cavendish Corporation, 1994)
Describes colonial history from the point of view of minorities and women
Keywords: Juvenile literature-History-Colonial period (1600 to 1775)-Social life and customs-Indians of North America-Pluralism-Social sciences-Minorities-United States-Nonfiction